Konsep Pendidikan Akhlak Siswa Menurut Habib Abdillah Bin Al-Haddad dalam Kitab Adabu Sulukil Murid - Muhammad Izhar Ar-rasyid Manik (EduInovasi: Journal of Basic Educational Studies, 2024)
The aim of this research is to analyze the ideal students in practicing muamalah in everyday life both in the classroom and outside the classroom, as we find in the current era the morale of students is experiencing a decline, and here we can find out the relevance of Habib Abdillah's thoughts bin Alawi al Haddad in the book of adabu sulukil pupil, this research uses a literature review or library research. This research covers how Habib abdillah bin alawi al haddad thinks about ideal students and educational methods in the book of adabu sulukil pupil, which is really needed for improve the morality of students to become good individuals and have good morals so that one of the goals of learning is achieved. The results of this research show that an ideal student is a form of education discovered by Habib Abdullah bin Alawi al-Haddad which can be said to be very practical. And guided by the Koran and Al Hadith.